Evaluation of Methods Used to Study the Impact of Innovation on Enterprise Value - Piotr WANICKI; Bartłomiej NITA (Communications of International Proceedings, 2021)
The main goal of the paper is to critically review the concepts of studying the impact of the implementation of innovation projects on the value of the company and their critical assessment, as well as to identify the conditions affecting the choice of an appropriate method for valuing innovation projects. The paper explains the specificity of innovation projects and then discusses trends in methods used to study the impact of innovation on company value. It then critically compares three methods, namely the risk adjusted NPV method, the real options valuation method and the Venture Capital method. It also reviews the leading studies on assessing the impact of innovation projects on enterprise value. Finally, conditions affecting the choice of valuation method for companies implementing innovative projects are identified
Keywords: enterprise value; innovation projects; valuation method